From bench scale to kilolab production of renewable ferulic acid-based bisphenols: optimisation and evaluation of different purification approaches towards technical feasibility and process environmental sustainability. Issue 3 (28th March 2017) - Teixeira, A. R. S.; Willig, G.; Couvreur, J.; Flourat, A. L.; Peru, A. A. M.; Ferchaud, P.; Ducatel, H.; Allais, F.
Abstract : Scaling-up a process is not always trivial. Technical synthetic feasibility, yield and environmental impact must be assessed. Abstract : In an earlier work by the authors, a new class of non-toxic and renewable bisphenols able to substitute bisphenol A and exhibiting potent antioxidant and antiradical activities has been prepared from ferulic acid through chemo-enzymatic pathways at bench scale. Scaling-up a process is not always trivial and straightforward. Technical feasibility of the synthesis and overall process yield must be assessed. All decisions should be justified regarding technical constraints and environmental sustainability. This work is focused on the kilolab production of bis- O -dihydroferuloyl 1, 4-butanediol (BDF ), one of the very promising renewable bisphenols. Recrystallization and organic diananofiltration in a single stage (SSD) and two stages (TSD) were compared taking into account the previous considerations. As a result, the synthesis and purification ofBDF by recrystallization were successfully scaled-up at the kilolab scale, with a significant improvement in the overall yield obtained (from 63% at the labscale to 84% at the kilolab scale) for a purity grade of 95%. To assess organic diananofiltration as an alternative purification method, a set of 6 commercial organic solvent resistant membranes was evaluated. Starting from a solution (1 g L −1 ) containing 80% (w/w) of BDF and 20% (w/w) of an excess reagent (ethyl dihydroferulate, EtDFe ), GMT-oNF1 membrane showed the ability to discriminate them. A two-stage membrane diafiltration (TSD) in cascade was proposed, with a drastic increase in the product yield observed (from 77% in a single stage to 95%) without compromising its final purity (95%). Since solvent recycling has a significant impact on the process sustainability, a nanofiltration step for solvent recovery was assessed. 90% of the solvent was recovered with a level of impurities lower than 1%. Recrystallization and all filtration-based processes were compared in terms of green metrics such as mass and solvent intensity and energy consumption. Results showed that only the integration of solvent recycling in filtration-based processes and the use of a concentrated starting solution (150 g L −1 instead of 1 g L −1 ) may lead to similar magnitude values observed for recrystallization. Thus, even being a less energetically intensive process (4-fold), the TSD is still a solvent intensive process (3-fold), which is inevitably reflected in a higher environmental footprint (evaluated by LCA).